ANALISIS KESENJANGAN UNTUK MENGUKUR KUALITAS PELAYANAN PADA MALL PELAYANAN PUBLIK (MPP) - Annisa Firdausi Fikri; Ertien Rining Nawangsari (Jurnal Governansi, 2023)
Bangkalan Regency is one of the regions in East Java that has a Public Service Mall (MPP). In 2018 basic services in Bangkalan are still not optimal, as an effort to improve service quality with MPP Bangkalan district. This study aims to measure service quality based on the service quality theory of Parasuraman, Zeithaml, and Berry with gap analysis 5 which is measuring the performance and expectations of service users, namely the community. The Servqual (Service Quality) model developed by Parasuraman, Zeithaml, and Berry, is the most widely used when measuring the quality of public services (B. Engdaw, 2022). The method used is descriptive quantitative using primary and secondary data with data collection techniques questionnaire, observation and documentation. The results showed that the service quality of MPP Bangkalan district was negative or not good because the average community expectation (public expectations) was greater than the performance (public perception) of MPP Bangkalan District with the highest gap on the responsiveness dimension (-0.01).